A selective review of knowledge-based approaches to database design - Shahrul Azman Noah; Michael Lloyd-Williams (Information Research: An International Electronic Journal)
The inclusion of real world knowledge or specialised knowledge has not been addressed by the majority of the systems reviewed. ODA has real world knowledge provided by using a thesaurus-type structure to represent generic models. Only NITDT includes the specialised knowledge in its knowledge base. NITDT classified its knowledge into application specific, domain specific and general knowledge. However the literature does not discuss in detail how this knowledge is applied during the design session. One of the key factors that distinguish computer-based expert systems from human experts is that the latter apply not only their specialised expertise to a problem but also their general knowledge of the world. NITDT is the only system reviewed here that holds any form of internal domain specific knowledge, which can be easily augmented, enriched and updated, as required. This knowledge allows the designer to be an active participant along with the user in the design process and significantly eases the user task. The inclusion of real world knowledge and specialised knowledge is an area that must be further addressed before intelligent tools are able to offer a realistic level of assistance to the human designers.